(untitled) (The Peerian Journal, 2023)
This article analyzes the dramatic work of the character of Ahmad Farghani. The drama "Ahmed Farghani" by Ibrahim Rahim was analyzed. The object of research is a historical figure, that is, Ahmad Farghani. In the article, the ideas put forward through the artistic image of Ahmad Farghani were revealed